Reconstruction of the national economy post-covid-19 pandemic: Critical study of tax reforms in Indonesia - Budi Ispriyarso; Kadek Cahya Susila Wibawa (Cogent Social Sciences)
Health, education, tourism, industry, public services, and the economy were all negatively impacted by COVID-19-related government actions. Consequently, they affected the economy. The state’s existence is required to alleviate the adverse consequences of COVID-19. Government activities in the tax sector are crucial to the nation’s economic development. The government accomplishes this in taxation by providing tax incentives and relief, as specified in tax regulations. Following the COVID-19 pandemic, this report assesses the Indonesian government’s economic recovery taxing strategies. The research employs the paradigm of Critical Legal Theory and the Socio-Legal research technique. The study results indicate that COVID-19 has affected virtually every industry in Indonesia, not simply the health sector. The coronavirus pandemic severely hit the economic sector with only 2.97% growth. The government’s tax policy for economic recovery due partly to the COVID-19 Pandemic is executed using tax instruments that provide incentives and various tax payment reductions to encourage the economy. Generally speaking, tax incentives have a favorable impact on the success of this method for giving tax relief and tax incentives as part of the National Economic Recovery programme. Taxpayers have a favourable opinion of incentive programmes. Taxpayers that take advantage of tax benefits have, on average, more extraordinary local sales performance, exports, turnover, local purchases, and imports. However, this tax incentive programme has led to a decline in state tax revenue. The government must accept this risk to fulfil its objective of stimulating the economy.